Monosomy 1p36 breakpoint junctions suggest pre-meiotic breakage–fusion–bridge cycles are involved in generating terminal deletions - Ballif, Blake C.; Yu, Wei; Shaw, Chad A.; Kashork, Catherine D.; Shaffer, Lisa G. (Human molecular genetics, 2003)
Terminal deletions of 1p36 result in a mental retardation syndrome that is presumably caused by haploinsufficiency of a number of genes. Although monosomy 1p36 is the most commonly observed terminal deletion syndrome in humans, the molecular mechanism(s) that generates and stabilizes terminal deletions of 1p36 is not completely understood. Our previous molecular analysis of a large cohort of monosomy 1p36 subjects demonstrated that deletion sizes vary widely from ∼1 Mb to >10.5 Mb in the most distal portion of 1p36 with no single common breakpoint. In this report, we have identified the precise breakpoint junctions in three subjects with apparently pure terminal deletions of 1p36 ranging from 2.5 to 4.25 Mb. These junctions revealed one deletion to be stabilized by telomeric repeat sequences and two to have terminal deletions associated with cryptic interrupted inverted duplications at the ends of the chromosomes. These interrupted inverted duplication/deletion breakpoints are reminiscent of those seen in tumor cell lines that have undergone breakage–fusion–bridge (BFB) cycles leading to gene amplification. We propose a pre-meiotic model for the formation of these deletions in which a terminally deleted chromosome is generated in the germ line and passes through at least one BFB cycle to produce gametes with terminal deletions associated with interrupted inverted duplications. These data suggest that, on a molecular level, seemingly pure terminal deletions visualized cytogenetically may be more complex, and BFB cycles may play an important role in generating terminal deletions associated with genetic disease in humans.